2016
DOI: 10.1016/j.juogr.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Using experimental design and response surface methodology to model induced fracture geometry in Shublik shale

Abstract: The Triassic Shublik Formation of the Alaska North Slope is a world-class resource rock and has been identified as the major source of many of the conventional hydrocarbon accumulations on the North Slope, including Prudhoe Bay. Recent interest in the Shublik as a potential shale resource play has highlighted the need for robust hydraulic fracture modeling and simulation of the interval, but little geologic information is available because of the remote nature of the region and the complex character of the Shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…As far as we know, it is the first time to e fractured coal has the characteristics of plastic deformation and ductile fracture, which will cause complex nonlinear seepage response in the coal matrix and the coal discontinuities. Obviously, the theory of linear elastic fracture mechanics [7], elastic damage mechanics [11], and fluid-solid coupling model based on Darcy's law [31] cannot fully reflect the nonlinear mechanics and seepage characteristics mentioned above. At the same time, most numerical models do not consider the joint effect of D op , i w on HF area in coal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, it is the first time to e fractured coal has the characteristics of plastic deformation and ductile fracture, which will cause complex nonlinear seepage response in the coal matrix and the coal discontinuities. Obviously, the theory of linear elastic fracture mechanics [7], elastic damage mechanics [11], and fluid-solid coupling model based on Darcy's law [31] cannot fully reflect the nonlinear mechanics and seepage characteristics mentioned above. At the same time, most numerical models do not consider the joint effect of D op , i w on HF area in coal.…”
Section: Discussionmentioning
confidence: 99%
“…ey found that the small stress difference and small elastic modulus difference of adjacent rock formation would lead to the interface strongly hindering the HF propagation. Based on the theory of elastic damage mechanics, Poludasu et al [7] and Xue et al [8] established a two-dimensional numerical model for the problem of HFs crossing the interface of the layered rock mass. ey found that only when the interface strength is relatively high would HFs will pass through the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental designs have been widely used in petroleum engineering studies for inverse problems (Ouenes et al 1994), reserve estimation (Imrie and Macrae, 2014), uncertainity analysis (Segnini et al 2014;Ambastha, 2014), sensitivity analysis (Yu and Sepehrnoori, 2014), and proxy model development (Poludasu et al 2015).…”
Section: Figure 12-design Parameters Selected For Sensitivity Analysismentioning
confidence: 99%
“…The statistical significance of individual input variable on the outcome can be estimated through the absolute magnitude of its regression coefficient (Poludasu et al 2015). We have two different sets of regression matrices, each representing the statistical significance of the input parameters on their respective fracture wing.…”
Section: Figure 12-design Parameters Selected For Sensitivity Analysismentioning
confidence: 99%